The Effect of Self-Efficacy and Career Motivation on Generation Z’s Work Readiness in Bekasi City - Siti Dewi Winata (Journal of Business and Management Inaba, 2026)
This research investigates the influence of self-efficacy and career motivation on the workforce preparedness of Generation Z individuals residing in Bekasi City. Adopting a quantitative framework with a descriptive-explanatory approach, the study employed a non-probability purposive sampling strategy, yielding a sample of 97 respondents calculated using the Lemeshow formula. Primary data were gathered through a 5-point Likert scale questionnaire and subsequently subjected to multiple linear regression analysis. The analysis demonstrates that self-efficacy has a notably positive and statistically meaningful effect on work readiness. Similarly, career motivation exhibits a positive and significant impact, with a relatively stronger contribution than self-efficacy. When assessed collectively, the two independent variables exert a substantial simultaneous influence on work readiness, reflected in an R² coefficient of 0.857—indicating that the model accounts for 85.7% of the total variance. The practical implications highlight the necessity of reinforcing intrinsic psychological attributes, namely self-efficacy, and career motivation, to boost the employability of Gen Z. Hence, academic institutions should design educational programs that prioritize soft skills development and structured career planning, ensuring that graduates are better equipped to meet labor market demands.